2022
DOI: 10.1093/oncolo/oyac176
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Profiling of Cell-Free DNA in Men With Advanced Prostate Cancer: Differences in Genomic Landscape Based on Race

Abstract: Advanced prostate cancer (aPC) in Black men was reported to present with aggressive features and to be associated with poor prognosis. Herein, we compared the cell-free DNA (cfDNA) genomic landscape of aPC in Black vs White men. Patients (pts) with aPC from 6 academic institutions and available cfDNA comprehensive genomic profiling (CGP) were included. Association between mutated genes and race was evaluated using Barnard’s test and a Probabilistic Graphical Model (PGM) machine learning approach. Analysis incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Another study revealed disparities in the adoption of cell-free fetal DNA (cffDNA) screening, particularly noting differences between Hispanic and White women [62]. Furthermore, investigations into the genomic landscape of cell-free DNA in men with advanced prostate cancer have unveiled distinctions based on race [63]. These findings collectively suggest noteworthy racial and ethnic variations in both cell-free DNA levels and the adoption of cf-DNA screening.…”
Section: Ethnic Differences In Cell-free Dnamentioning
confidence: 99%
“…Another study revealed disparities in the adoption of cell-free fetal DNA (cffDNA) screening, particularly noting differences between Hispanic and White women [62]. Furthermore, investigations into the genomic landscape of cell-free DNA in men with advanced prostate cancer have unveiled distinctions based on race [63]. These findings collectively suggest noteworthy racial and ethnic variations in both cell-free DNA levels and the adoption of cf-DNA screening.…”
Section: Ethnic Differences In Cell-free Dnamentioning
confidence: 99%
“…Furthermore, MYC amplification is associated with a higher Gleason grade and unfavorable prognosis in patients with PCa [148,149]. Interestingly, alterations in MYC are more frequently reported in black men than white men [149,150]. MYC overexpression was identified as an early event in PIN [151].…”
Section: Myc a Master Regulator Of Transcriptionmentioning
confidence: 99%
“…Beyond tissue analysis and imaging, MYC copy-number gain is detectable in cell-free DNA (cfDNA) isolated from blood [149,150] and urine [156], opening the potential of MYC to be used as a circulating biomarker. The detection of MYC levels in bodily fluids, such as blood or urine, may provide a less invasive method for diagnosing and monitoring PCa when compared to biopsy from a single site [156].…”
Section: Diagnostic Potential Of Mycmentioning
confidence: 99%
“…Blood-based cfDNA analysis of the androgen receptor (AR) gene can help predict resistance to enzalutamide and abiraterone in metastatic castration-resistant prostate cancer (mCRPC) [28]. Furthermore, the genomic profiling of cfDNA has shed light on differences in the genomic landscape between Caucasian and African American PCa patients, highlighting a higher number of alterations in genes like AR, EGFR, MYC, FGFR1, and CTNNB1 in African American patients [29].…”
Section: Introductionmentioning
confidence: 99%